Identifikasi Karakter Morfologi Tanaman Durian (Durio zibethinus Murr ) Lokal Kerinci - Jasminarni Jasminarni; Trias Novita; Evita Evita (Universitas Batanghari, 2023)
The durian plant (Durio zibethinus Murr) is knownas a wet tropical fruit native to Indonesia, with erratic production throughout the year. In Indonesia, durian plants have different harvest seasons. Durian is very popular with many people, so that some call it the king of fruits or the queen of fruits. Besides being sweet, fragrant with yellowish-white flesh and rich in colories, vitamin, fat and protein, the stems can also be used as building materials. Sitinjau Laut, Keliing Danau dan Danau Kerinci sub-districts are centers of durian production in Kerinci Regency, where the types of durian produced have different characteristics, so it is necessary to select from these various varieties, so that the types of durian that have the most superior characteristics and have productivity tall one. The method used in this study consisted of participatory observation methods and interviews with village officials, village communities and durian farmers in the three sub-districts to obtain descriptive data. Based on the results of interviews and field investigations, this type of local kerinci durian is still commonly found in community garden and needs to be rescued because it is difficult to track down and most of them are old. The forms types of local durians in Kerinci Regenncy vary greatly, each has advantages and disadvantages.